A low power transmission model based UWB technology for BAN applications - Suwan, Supakorn; Southisombath, Khamphoui; Promwong, Sathaporn (My University, 2020)
Low power transmission technology is ones of major concern in new wireless network (NWN) systems. The impulse radio is a potential technology to apply with body area network systems due to its transmit signal as impulse radio, which has low transmitted power. UWB gain high popular attention in short-range wireless communications development. Major kinds of application are able to used with UWB, e.g., wireless medical sensors networks, entertainment devices, and wireless localization. Information transmission in BAN systems is important for a reliable and accuracy in a actual used of medical sensors. In this research, the evaluation of UWB transmission model with human is introduce for analyze a distortion due to human body effect. The template waveform is proposed at the receiver side to achieve high level of SNR. The proposed model is very useful for the evaluation and design of wireless medical sensor networks including actual human body effect.
Keywords: BAN; Low power; UWB; WBAN; Wireless medical